On Whitman - Williams, C. K. (Charles Kenneth), 1936-2015 (Writers on writers., 2010)
In this book, Pulitzer Prize-winning poet C.K. Williams sets aside the mass of biography and literary criticism that have accumulated around the work and person of Walt Whitman, and attempts to go back to Leaves of Grass as he first encountered it, to explore why Whitman's epic "continues to inspire and sometimes daunt" him. The result is a personal reassessment and appreciation of one master poet by another, as well as an unconventional and brilliant introduction--or reintroduction--to Whitman. In brief, thematic chapters with many quotations from Leaves of Grass, Williams explores.